The feasibility of relaxation-enhanced angiography without contrast and triggering for preprocedural planning of transcatheter aortic valve implantation - Wang, Rui; Liu, Xinmin; Yao, Jing; Schoepf, U. Joseph; Griffith, Joseph; Wang, Jiayang; Lian, Jianxiu; Jiang, Ke; Song, Guangyuan; Xu, Lei (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiovascular MRI is advantageous in transcatheter aortic valve implantation (TAVI) planning. This study aimed to evaluate the feasibility of comprehensive non-contrast MRI [relaxation-enhanced angiography without contrast and triggering (REACT)] combined with a three-dimensional whole-heart MRI protocol for preprocedural planning of TAVI vs. computed tomography angiography (CTA). Methods Thirty patients with severe aortic stenosis were prospectively enrolled. The anatomical properties of the aortic root anatomy, including the perimeter and area of the virtual aortic valve annulus and coronary heights, were determined from 3D whole-heart MRI and cardiac CTA (CCTA) images, respectively. The diameters of the aorta (thoracic and abdominal aorta) and iliofemoral arteries were measured from REACT and aortic CTA (ACTA) images, respectively. A paired t-test was used to compare these two modalities. Bland–Altman plots were used to assess cardiovascular MRI and CTA measurements. Transcatheter heart valve (THV) sizing was performed based on CCTA measurements and compared with 3D whole-heart MRI measurements. The extent of annular calcification on 3D whole-heart MRI images was evaluated by a four-point grading scale and compared with CCTA data. Results All 30 patients completed CTA and cardiovascular MRI examinations, with the TAVI procedure being administered in 25 patients. The mean acquisition time of the comprehensive MRI protocol was 18 ± 3.2 min. There were no significant differences between ACTA and REACT data in regard to the diameters of aortic and iliofemoral arteries, including the ascending thoracic aorta (37 ± 4.6 mm vs. 37.7 ± 5.2 mm, p = 0.085), descending thoracic aorta (24.3 ± 2.8 mm vs. 24.3 ± 2.8 mm, p = 0.832), abdominal aorta (20.9 ± 2.5 mm vs. 20.8 ± 2.5 mm, p = 0.602), bilateral common iliac arteries (right: 8.36 ± 1.44 mm vs. 8.42 ± 1.27 mm, p = 0.590; left: 8.61 ± 1.71 mm vs. 8.86 ± 1.46 mm, p = 0.050), and bilateral femoral arteries (right: 6.77 ± 1.06 mm vs. 6.87 ± 1.00 mm, p = 0.157; left: 6.75 ± 1.02 mm vs. 6.90 ± 0.80 mm, p = 0.142). Both modalities showed similar aortic valve morphology and semi-quantitative valve calcification (all, p's > 0.05). Overall agreement for implanted THV was found in all 25 (100%) patients assessed with both modalities. Conclusion REACT combined with 3D whole-heart MRI enables reliable measurements of aortic root anatomy, annular calcification, and aorta and iliofemoral access in patients under evaluation for TAVI.